Ecohealth Research in Practice Innovative Applications of an Ecosystem Approach to Health - Charron, Dominique F. (Insight and Innovation in International Development, 2012)
Nearly two decades after the United Nations Conference on Environment and Development (commonly called the Rio Summit), the world is still facing a profound need for development to alleviate poverty and improve human lives through more equitable access and use of resources and healthier environments. Understanding that human health depends on quality ecosystems, researchers are cutting a new path toward a more sustainable future. An ecosystem approach to health, integrating research and practice from such fields as environmental management, public health, biodiversity, and economic development, is based on an understanding that people are part of complex socio-ecological systems. Featuring case studies from around the world, Ecohealth Research in Practice demonstrates innovative practices in agriculture, natural resource management, community building, and disease prevention, reflecting the state of the art in research, application, and policymaking in the field. The book demonstrates how ecohealth research works and how it has led to lasting changes for the betterment of peoples' lives and the ecosystems that support them. Dominique F. Charron leads IDRC's program in Ecosystems and Human Health (Ecohealth), which examines the links between the environment and human health in the developing world. Dr. Charron holds a PhD in epidemiology and a Doctor of Veterinary Medicine from the University of Guelph. Canada's International Development Research Centre (IDRC) supports research in developing countries to promote growth and development. IDRC also encourages sharing this knowledge with policymakers, other researchers, and communities around the world. The result is innovative, lasting local solutions that aim to bring choice and change to those who need it most. ISBN: 978-1-4614-0516-0 Canada Wordmark.